PENGALAMAN CAREGIVER DALAM MERAWAT PASIEN PALIATIF DI PANTI WERDHA TULUS KASIH - Putri Raissa Hamidah; Nurhayati Siagian (Fakultas Ilmu Keperawatan Universitas Klabat, 2021)
Late adulthood or known as old age, is the final phase of the life development stage. Old age is often identified with a period of decline in various bodily functions and an impact on helplessness. Because of this, many elderly suffer from incurable and life-threatening diseases known as palliative diseases. Many families of elderly patients who have palliative diseases feel unable to care for their patients at home, and finally, choose to leave elderly palliative patients at the Wredha Home because patients depend on the help of others for care to fulfill their needs and to carry out their daily activities accompanied by a caregiver at the Wredha Home. This reasearch was to ascertain an expertises felt by caregivers in caring for palliative patients at the Tulus Kasih Home. This research uses qualitative methods, data collection using interview methods with structured guides, and a purposive sampling technique that includes four participants. The result of this study covered six themes: the caregiver's understanding of palliative patients, what the palliative patients needs, what difficulties the caregiver experiences when giving action to elderly palliative patients, the caregiver's response when having difficulty caring for palliative patients, what efforts are made by the caregiver when having difficulty caring for palliative patients, and the efforts made by the caregiver in increasing the action for palliative patients.